Policing faces:The present and future of intelligent facial surveillance - Miranda, Diana (2021)
In this paper, we discuss the present and future uses of intelligent facial surveillance (IFS) in law enforcement. We present an empirical and legally focused case study of live automated facial recognition technologies (LFR) in British policing. In Part I, we analyse insights from 26 frontline police officers exploring their concerns and current scepticism about LFR. We analyse recent UK case law on LFR use by police which raises concerns around human rights, data protection and anti-discrimination laws. In Part II, we consider frontline officers’ optimism around future uses of LFR and explore emerging forms of IFS, namely emotional AI (EAI) technologies. A key novelty of the paper is our analysis on how the proposed EU AI Regulation (AIR) will shape future uses of IFS in policing. AIR makes LFR a prohibited form of AI and EAI use by law enforcement will be regulated as high-risk AI that has to comply with new rules and design requirements. Part III presents a series of 10 practical lessons, drawn from our reflections on the legal and empirical perspectives. These aim to inform any future law enforcement use of IFS in the UK and beyond